Investigation on Occupational Hazards and Control Measures in an Optical Enterprise. Issue 1 (April 2020) - Lu, S; Shu, Y; Cen, Z; Du, W; Liu, Y
Abstract: In this paper, the hazard factors of an optical enterprise were analyzed, and the appropriate prevention and control measures were discussed. The field investigation and detection of occupational health was applied. The on spot monitoring results showed that the over-standard rate of acetone in the workplace was 10.0%, the over-standard rate of trichloroethylene was 25.0%, the over-standard rate of dichloromethane was 50.0%, and the over-standard rate of noise was 23.8%. Acetone, trichloroethylene, dichloromethane and noise were the key points of prevention and control in this optical enterprise. It was suggested that the ventilation system of the cleaning workshop should been improved comprehensively, and the workers' hearing protection measures should been increased to effectively protect their health.